Implementing patient-reported outcome surveys as part of routine care: lessons from an academic radiation oncology department. (2nd March 2017) - Rotenstein, Lisa S; Agarwal, Ankit; O'Neil, Kelly; Kelly, Andrea; Keaty, Maureen; Whitehouse, Colleen; Kalinowski, Barbara; Orio, Peter F; Wagle, Neil; Martin, Neil E
Abstract: Patient reported outcomes (PROs) are reports of health conditions that come directly from patients. Use of PROs has been associated with improved patient outcomes, enhanced quality of life, and reduced end-of-life spending. Yet there are still outstanding questions regarding the process of implementing PRO collection in routine practice. In this article, we describe the experience of selecting and implementing PROs in a multisite, multidisease academic medical center–based radiation oncology practice and demonstrate that such large-scale rollout is feasible. We establish that PROs can be implemented with minimal to no workflow delays, are generally seen as valuable by clinicians, and can enhance patient-doctor communication. We additionally detail the challenges involved in selecting clinically relevant PRO questionnaires and the centrality of physician buy-in, easy data access, and clear workflows to successful implementation.